Courses au pouvoir: the struggle over customary capital in the eastern Democratic Republic of Congo. Issue 1 (2nd January 2020) - Hoffmann, Kasper; Vlassenroot, Koen; Mudinga, Emery
ABSTRACT: This article analyses the production and reproduction of traditional chieftaincy in war-torn eastern DR Congo, through the case of a succession dispute in Kalima (South Kivu). Kalima has gone through two decades of political instability and violent conflict involving a plethora of local, national and regional actors. During this period of uncertainty and upheaval, the institution of traditional chieftaincy has remained politically salient. We argue, that this salience is conditioned by a widespread belief in the authenticity and sacredness of the institution of traditional chieftaincy and by the ethno-territorial imaginary of the Congolese political order. Both of these are historically produced through rituals, ceremonies and narratives of origin. They imbue the institution of traditional chieftaincy with charisma and enable customary chiefs to accumulate resources and exercise authority in a wide range of domains of public life in rural eastern Congo. Drawing on Pierre Bourdieu, we call this ability to rule through the notion of 'custom', customary capital. However, we also show that 'customary capital' does not automatically accrue to chiefs as a variety of internal and external actors vie for customary capital. As such it fluctuates over time as different actors move in and out of the capacity to legitimately wield customary capital.